Case Report: Primary Thoracic Low-Grade Fibromyxoid Sarcoma in a Young Girl Presenting With Mediastinal Mass Syndrome - Chan, Yat Chi; Kan, Amanda N. C.; Yuen, Liz Y. P.; Wan, Innes Y. P.; Fung, Kevin K. F.; Cheung, Yiu-fai; Leung, Karen K. Y.; Ku, Dennis T. L.; Liu, Anthony P. Y. (Frontiers in Pediatrics, 2022)
Low-grade fibromyxoid sarcomas (LGFMSs) are typically adult-onset tumors that arise from the extremities. Here, we report an exceptional case of primary thoracic LGFMS in an 8-year-old girl that resulted in mediastinal syndrome. In reporting this case, we discuss the clinical challenges, role of molecular profiling and review reported cases of pediatric thoracic LGFMSs.